Precooling does not improve 2,000-m rowing performance of females in hot, humid conditions - Taylor, L.; Mauger, A. R.; Watkins, S. L.; Fitch, N.; Brewer, J.; Maxwell, N. S.; Webborn, N.; Castle, P. C. (The Journal of Strength and Conditioning Research, 2014)
Precooling lowers skin (Tsk) and core temperature (Tre) and can improve performance in hot conditions, but has predominantly been studied in males. This study investigated the effects of precooling on self-paced 2,000-m rowing performance, within females, in hot, humid conditions. Eight physically active females (19.9 ± 1.5 years, 66.8 ± 3.1 kg, 30.0 ± 5.0% body fat) performed 2,000-m rows in a randomized order within 3 conditions {control (CONT) (20° C, 40% relative humidity [RH]); hot (HOT) (35° C, 60% RH); precooling (PREC) (35° C, 60% RH, preceded by precooling)}. The precooling condition consisted of 20-minute precooling with a cold water shower, followed by a 2,000-m row. In contrast, CONT and HOT consisted of 20-minute passive rest in place of precooling. Tre, Tsk, and power output were recorded every 100 m of the rows. Muscle temperature (Tmu) was recorded at baseline, after 20-minute passive rest/precooling and post-row. No differences were observed between conditions for performance time (CONT, 8.89 ± 0.45 minutes; HOT, 9.01 ± 0.55 minutes; PREC, 8.87 ± 0.48 minutes; p = 0.42). Mean Tre during the row was not different between conditions (CONT, 37.8 ± 0.2° C; HOT, 37.7 ± 0.3° C; PREC, 37.5 ± 0.2° C; p = 0.12; main effect), although lower Tre was observed at 1,600 and 1,800 m in PREC compared with HOT (p < 0.05). Tmu was significantly reduced after precooling (p = 0.03). Precooling did not enhance 2,000-m rowing performance, despite differences in Tre, Tsk, and Tmu. The lack of observed improvement in rowing performance after cold shower precooling may have been due to the short exercise time. An improvement in performance may have been observed using an alternate method of precooling, which has been shown to be ergogenic in other sports.